Hepatitis C Virus (HCV) and its Genetic Diversity in clinical Isolates from Uttarakhand Population - Kuriyal, Monika; Bhandari, Anjali; Suman, Aaryansh Kumar; Shootha, Dheeraj; Gairola, Yati; Sharma, Narotam; Nautiyal, Satish Chandra (Journal of Drug Delivery and Therapeutics, 2019)
Hepatitis C is major cause of chronic liver disease. It has been recognised as a global health problem because of the progression to cirrhosis and hepatocellular cancer. Quantization and genotyping of HCV RNAs are important to determine the optimal duration of anti-viral therapy and predict likelihood of response. Total 77 samples were tested biochemically, serologically and molecular assay (Roche COBAS TaqMan 48 Real Time PCR). Out of 77 cases 33(42.85%) were with high viral load (>103IU/ ml of HCV RNA) and low viral load (below 103IU/ml) 2 (2.59%) and 42 (54.54%) were target not detected (below 25 IU/ml). Genotype 3 was prevailed with 68.42% out of 35 cases followed by HCV genotype 15.78% in 1, 5.26% in 2 and 6, 2.63% in 1b and 4. In addition, our studies showed that genotype 1, 2, 4 and 6 (mixed genotype was detected in 1 cases with viral load 6.62 × 108IU/ml). Total protein content in serum in all the cases was average except 04 cases that was having low protein content. 02 cases were having low uric acid content that was having high viral load. From all high positive (high viral load) cases which were further diagnosed for their genotyping in which genotype 3 was prevalent following by genotype1, 1b, 2, 4 and  6. Study signifies the gene based diagnosis and its clinical relevance for the proper management of the patients.Keywords: Hepatitis, Chronic, Real Time PCR, Hepatocellular Carcinoma, Serology